The Effect of Phytobiotics and Lactobacillus acidophilus of The Diet on Protein Digestibility, Egg Calcium and Protein Mass and Egg Content Weight of Laying Hens - Yunianto , Vitus Dwi; Yuniasari, Finas Anggi; Suthama, Nyoman; Krismiyanto, Lilik (Indonesian Soil Science Society of South Sumatra in Collaboration With Soil Science Department, Sriwijaya University, 2025)
The study aimed to assess the feeding of a mixture of onion peel flour, garlic peel, bay leaves and Lactobacillus acidophilus on crude protein digestibility, calcium mass and egg protein and egg weight in laying hens. The livestock used were 72-week-old Isa Brown strain laying hens totaling 144 birds with an average body weight of 1824 ± 126.15 g. The study was arranged in a completely randomized design (CRD) with 6 treatments and 4 replicates, each experimental unit consisted of 6 birds. The treatment given is T0 = basal diet, T1 = basal diet + 1.2 ml Lactobacillus acidophilus, T2 = basal diet + phytobiotics 2%, T3 = basal diet + phytobiotics 2% + 1.2 ml Lactobacillus acidophilus, T4 = basal diet + phytobiotics 4% + 1.2 ml Lactobacillus acidophilus, T5 = basal diet + phytobiotics 6% + 1.2 ml Lactobacillus acidophilus. Parameters observed included protein digestibility, egg protein and calcium mass, and egg content weight. Data were analyzed for variance, if the treatment had a significant effect (p<0.05) followed by Duncan’s test at the 5% significance level. The results showed that giving a mixture of onion peel flour, garlic flour, bay leaves and Lactobacillus acidophilus had a significant effect (p<0.05) on protein digestibility, protein mass and egg calcium and egg weight in laying hens. The conclusion is that the addition of 2% phytobiotic plus 1.2 ml Lactobacillus achidophilus to the ration of laying hens can effectively increase protein digestibility, egg calcium mass and egg weight in laying hens.